Determinants of religious experience among university students. - Głaz, Stanisław (Studia Psychologica: Theoria et praxis, 2004)
It is suggested that some personality features, one’s attitude towards preferred values, emotional condition or the intensity of one’s religiousness can either foster or impede religious experiences of a human being. The research was carried out in 2002. All students declared they were believers and observed religious experience in their lives. 139 correctly filled in questionnaires were analysed. The sample consisted of 46 men and 30 women from the Vocational High School in Nowy Sącz and 30 male and 33 female students of philosophy at Ignatianum University in Kraków. Their age was within the range 22 to 25. The author, interested in the issues of values, personality and religious experience of a human being tried to answer the following questions: Do the independent variable, sex and the field of study differentiate the intensity of the effects of experience of God’s presence, God’s absence, the feelings arisen by such experience, commitment to religious matters and emotional condition of the examined people? Do the independent variables, sex and the field of study differentiate the preference of final values? Which (and to what extent) of the independent variables taken into account in KKE and SZR tests have influence on the dependent variables, the effects of the experience of God’s precence (OB) and the effects of the experience of God’s absence (NOB)? As it was found, sex differentiates some dimensions of emotional structure, of religiousness and religious experiences taken into account in the research. Regression analysis shows that the most crucial influence of essential independent variables on the dependent variables (concerning the effects of religious experiences) have variables which concern religiousness. The other independent variables have lesser influence on the dependent variables (OB, NOB).